Trend in Science Education Assessment Instruments: A Systematic Literature Review (2014-2024) - Anisa Ayu Solikah; Sulistyo Saputro; Sri Yamtinah (STAI Hubbulwathan Duri, 2025)
Assessment in education plays a critical role in evaluating not only students’ cognitive understanding but also broader 21st-century skills such as critical thinking, collaboration, and communication. However, traditional assessments often prioritize conceptual knowledge over these essential skills. This study investigates current trends in assessment within science education to identify gaps and potential improvements. A Systematic Literature Review (SLR) was conducted using articles sourced from the Google Scholar database between 2014 and 2024. The search employed keywords such as “assessment learning” and “science learning.” A total of 992 articles were initially collected, which were then filtered based on relevance and quality, resulting in 76 eligible articles. Data analysis was supported by Publish or Perish software and visualized using VOSviewer. The VOSviewer analysis produced network, overlay, and density visualizations that revealed a predominant focus on conceptual understanding in science education assessments. This focus likely stems from the relative ease of standardizing and measuring conceptual knowledge compared to more complex 21st-century skills. Other dimensions, such as creativity, collaboration, and problem-solving, were significantly underrepresented in the literature. The findings highlight a need to diversify assessment strategies in science education to better reflect 21st-century learning goals. This review provides a foundation for future research aimed at developing comprehensive assessment instruments that go beyond cognitive evaluation and support holistic student development.